Coworking as a New Innovation Scenario from the Perspective of Mature Organisations - Barbara Josef; Andrea Back (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
The proposed literature review looks at the relatively young phenomenon coworking*, its various manifestations and value scenarios from a company's perspective. It aims at giving an overview of the current research on coworking and in particular of the different disciplines and perspectives from which coworking has been researched recently, with a particular focus on coworking as “third places” for mature organizations (in contrast to the usage by startups/freelancers). Based on the cross-disciplinary literature review a classification will be derived which clusters the analysed contributions into different key constructs that are relevant when looking at coworking as an alternative work scenario for mature organizations (e.g. spatial patterns, community management, leadership culture, enterprise social networking etc.). The result of the literature review and the derived synthesis aims at serving companies as a framework and orientation aid when ev aluating the different business value scenarios of coworking. The paper aims at contributing to the overall question, how companies can drive a culture of innovation and business agility by adapting their work environment and offered work scenarios. The authors have already conducted a first coworking study in Switzerland, examining an experiment of Microsoft and the largest local telco provider. Whereas this preliminary study allowed to identify the most relevant opportunities and challenges of coworking from a company's perspective, a more thorough analysis of existing research contributions is needed to develop an instrument which serves companies as orientation guide in a process of work culture transformation.
Keywords: 650; Coworking; Innovation culture; Serendipity; Classification